Phân tích đa thức thành nân tử
1) a*(b^3-c^3)+b*(c^3-a^3)+c*(^3-b^3)
2)x*(y^2-z^2)+y*(z^2-x^2)+z*(x^2-y^2)
3)x^2*(y-z)+y^2*(z-x)+z^2*(x-1)
1) Đề nhầm không ?
Phải là : [tex]a(b^{3}-c^{3})+b(c^{3}-a^{3})+c(a^{3}-b^{3})[/tex] chứ, nhỉ ?
Nếu vậy có :
[tex]a(b^{3}-c^{3})+b(c^{3}-a^{3})+c(a^{3}-b^{3})[/tex]
=[tex]a(b^{3}-c^{3})-b[(b^{3}-c^{3})+(a^{3}-b^{3})]+c(a^{3}-b^{3})[/tex]
=[tex]a(b^{3}-c^{3})-b(b^{3}-c^{3})-b(a^{3}-b^{3})+c(a^{3}-b^{3})[/tex]
=[tex](a-b)(b-c)(b^{2}+bc+c^{2})+(c-b)(a-b)(a^{2}+ab+b^{2})[/tex]
=[tex](a-b)(b-c)(b^{2}+bc+c^{2})-(b-c)(a-b)(a^{2}+ab+b^{2})[/tex]
=[tex](a-b)(b-c)(b^{2}+bc+c^{2}-a^{2}-ab-b^{2})[/tex]
=[tex](a-b)(b-c)(bc+c^{2}-a^{2}-ab)[/tex]
=[tex](a-b)(b-c)(c-a)(a+b+c)[/tex]
Phần 2) và 3) tách tương tự !